2001
DOI: 10.1074/jbc.m100206200
|View full text |Cite
|
Sign up to set email alerts
|

Histone Hyperacetylation Induced by Histone Deacetylase Inhibitors Is Not Sufficient to Cause Growth Inhibition in Human Dermal Fibroblasts

Abstract: Use of specific histone deacetylase inhibitors has revealed critical roles for the histone deacetylases (HDAC) in controlling proliferation. Although many studies have correlated the function of HDAC inhibitors with the hyperacetylation of histones, few studies have specifically addressed whether the accumulation of acetylated histones, caused by HDAC inhibitor treatment, is responsible for growth inhibition. In the present study we show that HDAC inhibitors cause growth inhibition in normal and transformed ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 59 publications
4
45
0
Order By: Relevance
“…Previous studies have demonstrated that all classes of HDACi have similar effects on mitosis (Warrener et al, 2003;Stevens et al, 2008). SBHA (IC 50 12 g/ml) rapidly induced maximal histone acetylation when used at a concentration of 100 g/ml (Brinkmann et al, 2001;Gabrielli et al, 2004), and was used at this concentration throughout this study as a generic HDACi. Exposure of early embryos to HDACi resulted in mitotic defects, with loss of the uniform distribution of nuclei in the embryo, a phenotype similar that resulting from exposure to paclitaxel (Taxol; Bristol-Meyers Squibb, Princeton, NJ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that all classes of HDACi have similar effects on mitosis (Warrener et al, 2003;Stevens et al, 2008). SBHA (IC 50 12 g/ml) rapidly induced maximal histone acetylation when used at a concentration of 100 g/ml (Brinkmann et al, 2001;Gabrielli et al, 2004), and was used at this concentration throughout this study as a generic HDACi. Exposure of early embryos to HDACi resulted in mitotic defects, with loss of the uniform distribution of nuclei in the embryo, a phenotype similar that resulting from exposure to paclitaxel (Taxol; Bristol-Meyers Squibb, Princeton, NJ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This molecule has the ability, as do many other histone deacetylase inhibitors, to inhibit growth and induce apoptosis in a variety of tumor cell lines [42,118]. It was found however that histone acetylation alone could not account for the molecule's cytotoxic effect [119]. The molecule's properties appear instead to be the result of increased acetylation of Hsp90, which interferes with binding and stabilization of oncoproteins p53, Raf-1, and ErbB2.…”
Section: Acetylationmentioning
confidence: 99%
“…We made the remarkable observation that the broad specificity deacetylase inhibitor, trichostatin A, disrupted several HDAC⅐phosphatase complexes, suggesting a novel mechanism for coordinating protein phosphorylation and acetylation in mammalian cells. Because the increased histone acetylation elicited by TSA and other broad-acting deacetylase inhibitors is by itself insufficient to inhibit cell growth (21) and transformation (22), our data suggested that the disruption of HDAC⅐phosphatase complexes and the ensuing changes in protein acetylation and phosphorylation may together account for the anticancer activity of these compounds.…”
mentioning
confidence: 95%